دور التخطيط ألاستراتيجي في رسم مستقبل إقليم كوردستان - محمدأمين, إلياس طاهر (Journal of Legal and Political Studies, 2013)
The Kurdistan Regional Government and distinctive situation of its political side, Stresses the need to put a comprehensive strategic plan to deal with the current situation and try to keep it serious. As well as to deal with the future and try to achieve the goals of political, economical and security relating to the independence of the region and the formation of an independent Kurdish state.In the way to put a strategic plan for the Kurdistan Region there are ranges of motives that supports, assists and facilitates the planning process. Including the security and the military stable situation that Region is go through, as well as the distinctive economic situation and the standard of Kurdish citizen living, and also the distinctive social and cultural situation of the Kurdistan Region from neighborhood states, and the absence of problems, ethnic, linguistic, religious and Sectarian. But despite these motives, there are a range of difficulties and impediments are exposed through the development of the strategic plan, which must Kurdistan Regional Government to exceed, including the non-obvious democratic process, and administrative political and economic corruption, and foreign interventions by regional neighboring countries, and also approaching of social problems of the disassembly of family and lack of emphasis on the customs and mores of Kurdish society, for Kurdistan Regional Government to work seriously to take advantage of the motives and overcome the difficulties, in order to achieve a better future for this region.
Keywords: Strategic Planning; future; Kurdistan Region; Government; Public Administration